Theoretical modelling of normal incidence sounds absorption coefficient of wood circular perforated panel due to resonance frequency - Dimon, Mohamad Ngasri (Faculty of Electrical Engineering, 2009)
Wood Perforated Panels (WPP) has been used as part of wall partition of an enclosed room particularly in mosques. Wood Circular Perforated Panels (WCPP) is the simplest form of WPP. Due to non-existence of reliable normal incidence sound absorption coefficient ( n ï?¡ ) for WCPP, the consideration of WCPP as a sound absorption material cannot be ignored. It is believe that the WCPP can act as sound absorption material as it has inherent capability to allow sound waves to pass through easily. This research investigate the normal incidence sound absorption coefficient ( n ï?¡ ) of WCPP due to resonance frequencies using numerical modelling technique. The numerical experiments are conducted using Boundary Element Method (BEM) since it is a powerful computational method. It is among the most recent tool and providing numerical solutions for Acoustic Engineering design. The complexity of the design and simulation of WCPP is then resolved using quarter modelling technique. The perforation ratios investigated are 30% and 40%. The aperture creation begins with the calculation of aperture dimension. This dimension was calculated to resonate at 1 kHz, 2 kHz and 4 kHz with n = 1, 2 and 3. Then it is followed by modeling and compilation process for room with WCPP and empty room. n ï?¡ of WCPP due to resonance frequencies was calculated by dividing net sound intensity value in front of the circular panel with incident sound intensity obtained in empty room. From the numerical simulation result, it was found that n ï?¡ from 250 Hz to 500 Hz is mainly due to mass transfer. Whereas, from 2 kHz to 4 kHz, the n ï?¡ are contributed by its resonance frequency. At 1 kHz, it is shown that n ï?¡ value is in the transition state, between mass transfer and resonance frequency effect. The electroacoustics calculation of R,L,C of WCPP at 30 % and 40 % perforation ratio also shown that the RLC values are reasonably small and shall not affect to the n ï?¡ significantly.